Editor's Note - Animal Law Education - Meg Good (Legal Education Review)
Animal law teachers typically assert that an animal law classroom provides the ideal training ground for a law student. The purpose of this paper is to critically examine this assertion and, ultimately, to provide a supporting argument for the proposition that animal law is a unique vehicle for providing students with a high quality legal education. Legal education is characterised by distinct and competing discourses with respect to the nature of law teaching, including doctrinalism, vocationalism, corporatism, liberalism, radicalism and educationalism. The first part of the paper provides an overview of Foucauldian discourse theory and a description of each legal education discourse. The second part of the paper provides an examination of the distinctive features of an animal law curriculum and learning environment that make the subject an ideal setting for facilitating high quality student learning, regardless of the predominant discourse in operation.